Effect of Dance on Balance, Mobility, and Activities of Daily Living in Adults With Cerebral Palsy: A Pilot Study - Joung, Hee Joung; Yang, Hye Kyung; Lee, Yongho (Frontiers in Neurology, 2021)
The age-related decline in motor function with respect to balance and mobility may hamper the activities of daily living, quality of life, and social participation. Despite the importance of managing secondary conditions leading to premature aging, the literature regarding appropriate physical activity for adults with cerebral palsy (CP) is still scarce. Dance forms have emerged as an effective physical activity that improves balance and mobility in individuals with neurological conditions and boosts social engagement. However, its effect on adults with CP has yet to be examined. This pilot study aimed to examine the long-term effect of dance on improving balance and mobility in adults with CP. This single-cohort study included 10 adults with CP. They attended two 90-min-long creative dance sessions per week for 12 weeks. The outcomes measured effects on balance, mobility, balance confidence, and level of functional independence. These measurements were obtained at pre-intervention, post-intervention, and the 3-month follow-up. Outcome data of pre- to post-intervention and pre-intervention to 3-month follow-up were analyzed and compared. Statistically significant differences were found in the pre- and post-intervention displacement of the center of pressure (CoP) in the eyes-opened (EO) condition, timed up and go test (TUG), and Berg Balance Scale (BBS), Dynamic Gait Index (DGI), and Korean-Activity of Balance Confidence (K-ABC) scores. Significant improvements were also observed for the CoP-EO, BBS, TUG, DGI, and K-ABC between the pre-intervention and 3-month follow-up assessments. However, there were no significant differences in the CoP in the eyes-closed condition and Korean modified Barthel Index score. Participants expressed enjoyment without any pain or fatigue. Our findings suggest that dance may have a positive impact in improving balance and mobility and may consequently contribute to healthy aging in adults with CP.